'Are we famous or something?' Participatory Health Research with children using photovoice. Issue 3 (26th May 2020) - Abma, T. A.; Schrijver, J.
ABSTRACT: Photovoice is a child-friendly method used in Participatory Health Research (PHR) to put children in a subject position to drive the research and social change. Little is known about the actual experiences of doing photovoice related to health issues in a primary school context regulated by adults. The purpose of this article is to explore how children's voices can be genuinely taken into account in research and social change, and what the potentials and tensions are when using photovoice in schools. We present a case example of a PHR with primary school children using photovoice, and will focus on the lessons learned. Participating children were eager to tell their photostories, proud of their achievements, and felt 'seen' by adults, expressed in the phrase 'Are we famous or something?' Playful activities and concrete instructions helped children to create their own narrative. For the development of the children's critical consciousness reflexive participatory actions and photo-elicitation were crucial. Their visuals prompted discussion and led to actions and plans taking into account their perspectives. Tensions included the struggle to find a right balance between guidance and control, protection and respect for autonomy and preset system requirements. Reflexivity and creativity are required to handle such tensions.